State-owned enterprises in Uzbekistan: Taking stock and some reform priorities - Umidjon Abdullaev (Asian Development Bank Institute (ADBI), 2020)
The state is a major owner of industrial and commercial enterprises in Uzbekistan. State-owned enterprises (SOEs) dominate and have significant influence on the performance of most sectors in the economy, including natural resources, energy, manufacturing, telecommunications, transport, and agriculture. The purpose of this study is to review the economic weight and degree of presence of SOEs in the economy of Uzbekistan, analyze in detail governance mechanisms employed by the Uzbek government to manage its portfolio of commercial enterprises, and discuss the scope of Uzbekistan's past and ongoing privatization initiatives. A number of recommendations for addressing key issues identified in the paper are outlined.
Keywords: L32; O25; G34; 330; state-owned enterprises; governance; privatization